The Mediating Effect of Depression on the Relationship between Marital Satisfaction and Quality of Life in Women - Fatma Keskin Tore; Yurdagul Yagmur and Ebru Gul (Professor Despina Sapountzi-Krepia, 2024)
The Mediating Effect of Depression on the Relationship between Marital Satisfaction and Quality of Life in Women